Элементный состав Trifolium pratense L. ‘Skif 1‘ - Остапко, И.Н.; Купенко, Н.П. (Промышленная ботаника, 2002)
Element composition of Trifolium pratense L.‘Skif 1‘ above-ground part, including leaves and inflorescence, as well as roots of the named plant, having been grown in the Donetsk botanical gardens, Nat. Acad. Sci. of Ukraine has been examined. The data obtained are important for characterizing specifics of 29 chemical elements accumulation in T. pratense in the region. An unsignificant exceeding of sanitary standards as for Fe, Zn, Cr accumulation, with exclusion of Cd, has been fixed.